Thoughts Matter : Discovering the Spiritual Journey - Funk, Mary Margaret (Book collections on Project MUSE., 2012)
Cassian taught that real intimacy with God in prayer demands renouncing one's former way of life, the thoughts belonging to that former way of life, and one's very idea of God. In Thoughts Matter, Mary Margaret Funk focuses on the second of these: renouncing the thoughts belonging to one's former way of life. Her eight chapters focus on different thoughts: food, sex, anger, dejection, acedia (profound weariness of the soul), vainglory (taking credit for good actions), and pride. Funk explains well how failure to control these thoughts can undermine a spiritual life, and she instructs readers on how effectively to overcome these thoughts and to focus instead on thoughts in harmony with God's will. The result is an experience of joy, hope, and freedom from enslavement to human appetites. Readers will come away enlightened, strengthened, and inspired to delve more deeply into a life of intimacy with God.